ASSOCIATION BETWEEN MORPHOLOGICAL DIMENSIONS OF WATER POLO PLAYERS AND PLAY PERFORMANCE INDICATORS - Dragan Milanović; Dinko Vuleta (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The goal of the paper is to determine relevance of certain morphological parameters, understood as the dimensions of morphological status of water polo players, in relation to their game performance in the phases of defence and attack. The sample of subjects embraced 104 (aged 17-19 yrs) top-quality water polo players, members of junior selections from eight water polo clubs, who participated in the Adriatic League competition. The total variable sample consisted of the predictor variables (10) and two criterion variables based on the expert evaluations of the subjects' play in attack and defence. The associations between the predictor variables and play performance grades were established using regression analysis. The obtained results suggest the quantity of subcutaneous fat directly affects quality of playing in the phase of defence, meaning that the players with larger quantities of subcutaneous fat perform poorly in polyvalent defensive actions and demonstrate a low level of agility, both resulting in less effective play in defence. Although the quantity of subcutaneous fat has been recognized as the factor affecting play quality in attack as well, we obtained that it has smaller effect than in the case of defence. The probable cause of the afore-mentioned may be found in water polo players with a relatively greater amount of fatty tissue (hole sets), who are still highly efficient in attack tasks performance. Their situation-related efficiency is manifested in better positioning and position keeping, as well as in larger number of forced exclusions of the opponents, which contributes comprehen¬sively to attack efficiency.